(untitled) (Research, Society and Development, 2023)
Introduction: Human aging is a genetically designed phenomenon, which occurs dynamically, progressively and irreversibly, leading to a decline in functional and cognitive abilities. Changes in the body physiology of the elderly increase the risk of self-medication. The presence of polypharmacy among the elderly is very frequent due to the various pathologies they present. Objective: To trace the pattern of medication use in elderly people attended at UBS Campo Bello in the municipality of Gurupi-Tocantins. Methodology: An exploratory descriptive study was carried out with the elderly assisted at UBS Campo Bello in the municipality of Gurupi. Using simple random sampling, among the estimated number of participants, the first ones who accepted the invitation, answered a questionnaire and agreed with the TCLE terms, the collected data were analyzed using descriptive statistics. Results: Information was found on which drugs are used, whether polypharmacy is used, whether there are adverse effects or drug interactions between the drugs used. Final considerations: It was possible to observe the use of the main drugs in men and women over 60 years old, highlighting polypharmacy, which causes a serious risk to health, especially the health of the elderly. According to the evaluated studies, it is noted that the involvement of pharmaceutical professionals with in-depth scientific technical knowledge is increasingly important, evaluating adverse reactions and drug interactions. Recommends for future work, a more detailed research on the topic addressed.